FAKTOR - FAKTOR YANG MEMPENGARUHI KONSUMSI LISTRIK DI INDONESIA - Mutia Rosadi; Syamsul Amar (Universitas Negeri Padang, 2019)
This research aims to examine the factors that influence the consumption for electricity in Indonesia with the selected model is the Fixed Effect Model (FEM). The data used is panel data during the period 2014-2017, with the technique of collecting documentation data and library studies obtained from relevant institutions and agencies.The variables use are electricity tariff, income, number of household customer, and number of industrial customer. The research method used is Ordinary Least Square (OLS). The estimation results show that, electricity tariff have a negative and its not significant effect on the electricity consumption in Indonesia.s. Income, household customer, and industrial customer have a positive and significant effect on the electricity consumption in Indonesia. Meanwhile simultaneously electricity tariff, income, number of household customer, and number of industrial customer affect the electricity consumption in Indonesia.